2014
DOI: 10.12659/msm.889833
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of etomidate-induced myoclonus: Which is superior: Fentanyl, midazolam, or a combination? A Retrospective comparative study

Abstract: BackgroundIn this retrospective comparative study, we aimed to compare the effectiveness of fentanyl, midazolam, and a combination of fentanyl and midazolam to prevent etomidate-induced myoclonus.Material/MethodsThis study was performed based on anesthesia records. Depending on the drugs that would be given before the induction of anesthesia with etomidate, the patients were separated into 4 groups: no pretreatment (Group NP), fentanyl 1 μg·kg−1 (Group F), midazolam 0.03 mg·kg−1 (Group M), and midazolam 0.015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…Magnesium blocks NMDA receptor currents in a voltage-dependent manner by blocking the receptor channel. [ 16 17 18 19 ] Guler et al . compared low-dose magnesium and ketamin in preventing the injection pain of etomidate and found ketamin to be superior.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium blocks NMDA receptor currents in a voltage-dependent manner by blocking the receptor channel. [ 16 17 18 19 ] Guler et al . compared low-dose magnesium and ketamin in preventing the injection pain of etomidate and found ketamin to be superior.…”
Section: Discussionmentioning
confidence: 99%
“…When etomidate was first introduced in 1973, it was known as an agent with hypnotic properties that possessed minimal cardiovascular and pulmonary complications (1). Etomidate maintains hemodynamic stability and eliminates histamine release more profoundly than other drugs (2). Research has shown that using etomidate at a dose of 0.3 mg/kg does not cause significant changes in the cardiac stroke volume, heart rate, right atrial pressure, cardiac index, systemic and pulmonary vascular pressures, leading to the increasing use of this medication (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported the incidence of myoclonus in up to 80% of the times when it was administered. Myoclonus can be detrimental to full-stomach patients undergoing emergency surgery, patients with an open eye injury, and those with a history of cardiovascular disease (2,6). Although the mechanism of myoclonus is not fully understood, various medications have been used to prevent the occurrence of myoclonus (1), including fentanyl (2), benzodiazepines (7), rocuronium (8), opioids (9), Copyright © 2019, Author(s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, etomidate is the most appropriate drug in patients with compromised cardiopulmonary function because of its minimal cardiovascular and respiratory depressant effects, ( 18 ) however, etomidate has some side effects such as injection pain, adrenal suppression and myoclonus. Pretreatment with low dose of a hypnotic agent such as midazolam ( 19 - 21 ), reduces myoclonus. The incidence of myoclonus due to etomidate depends on the dosage and speed of injection ( 22 ).…”
Section: Introductionmentioning
confidence: 99%